2014
DOI: 10.4161/auto.32135
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy and chloroquine sensitivity by oncogenic RAS in vitro is context-dependent

Abstract: Chloroquine (CQ) is an antimalarial drug and late-stage inhibitor of autophagy currently FDA-approved for use in the treatment of rheumatoid arthritis and other autoimmune diseases. Based primarily on its ability to inhibit autophagy, CQ and its derivative, hydroxychloroquine, are currently being investigated as primary or adjuvant therapy in multiple clinical trials for cancer treatment. Oncogenic RAS has previously been shown to regulate autophagic flux, and cancers with high incidence of RAS mutations, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 37 publications
8
66
0
Order By: Relevance
“…32 However, cancers which harbor RAS mutations are not always sensitive toward treatment with autophagy inhibitors, and the expression of oncogenic RAS may even promote resistance toward autophagy inhibition in lung cancer cell lines. 33 Therefore, the relation between KRAS mut expression and sensitivity toward rLGALS9, may be specific for colon cancer. Besides the maintenance of tumorigenesis, the activation of autophagy is one of the mechanisms by which tumor cells acquire therapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, cancers which harbor RAS mutations are not always sensitive toward treatment with autophagy inhibitors, and the expression of oncogenic RAS may even promote resistance toward autophagy inhibition in lung cancer cell lines. 33 Therefore, the relation between KRAS mut expression and sensitivity toward rLGALS9, may be specific for colon cancer. Besides the maintenance of tumorigenesis, the activation of autophagy is one of the mechanisms by which tumor cells acquire therapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the autophagy pathway and its potent profibrotic effects suggest that autophagy may be a potential target for novel antifibrotic approaches. In the present study the autophagy inhibitor CQ was selected for the inhibition of the autophagy pathway for the following reasons: Firstly, it is able to diffuse across cell membranes, undergo protonation and accumulate in acidic organelles, such as lysosomes (29); secondly, it is a 4-aminoquinoline drug used in the treatment of numerous diseases; and thirdly, this approach allows broader inhibition of autophagy compared with targeting single autophagy proteins (30).…”
Section: Discussionmentioning
confidence: 99%
“…Given that autophagy plays context-dependent roles in cancer, the clinical benefits of targeting autophagy may be unpredictable. Consistent with this concern, a recent study showed that RAS mutation status alone might be insufficient to predict autophagy addiction and CQ sensitivity of cancer cells cultured in vitro (18). Hence, there is a need to define the optimum cellular contexts or identify new biomarkers that will aid in the therapeutic targeting of autophagy via lysosomotropic agents such as CQ or HCQ.…”
Section: Introductionmentioning
confidence: 99%